1986
DOI: 10.2527/jas1986.623857x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Utilization and Digestibility by Growing Steer and Goats of Diets that Contain Monensin and Low Crude Protein

Abstract: Two digestion and metabolism experiments were conducted to determine effects of monensin in low-protein diets. Monensin supplementation (27 mg/kg of diet dry matter) of steers (303 kg) fed 8.7% crude protein increased (P less than .01) apparent N digestibility and N retention and decreased (P less than .01) percentage of N apparently absorbed lost in urine. Apparent digestibilities of dry matter, gross energy and acid detergent lignin were increased (P less than .05). Digestibilities of neutral detergent and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
13

Year Published

1988
1988
2006
2006

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 0 publications
0
9
0
13
Order By: Relevance
“…Improvement of gain was much more pronounced in grazing cattle. Furthermore, the digestibility of grass was improved by feeding lasalocid, lysocellin, monensin and salinomycin (68,69,38,70,63). This variability in response between finishing and grazing cattle may be explained by two different feed intake mechanisms.…”
Section: Ruminantsmentioning
confidence: 99%
“…Improvement of gain was much more pronounced in grazing cattle. Furthermore, the digestibility of grass was improved by feeding lasalocid, lysocellin, monensin and salinomycin (68,69,38,70,63). This variability in response between finishing and grazing cattle may be explained by two different feed intake mechanisms.…”
Section: Ruminantsmentioning
confidence: 99%
“…Foi encontrada regressão linear (P<0,05) para os coeficientes de digestibilidade aparente, bem como para NDT, ED, MSD, PD e FDND, em que os valores se elevaram com o aumento dos níveis de monensina. Os coeficientes de digestibilidade apa- (SCHELLING, 1984;MEDEL et al, 1991) da MS e FDN, em novilhos canulados no rúmen e no duodeno (FAULKNER et al, 1985), da MS e EB em novilhos alimentados com dieta pobre em proteína (BEEDE et al, 1986) e da MS, PB e FB, em dietas altas e baixas em fibras, em novilhos Holandeses (ARAUJO-FEBRES e FERNÁNDEZ, 1991). Houve também aumento na digestibilidade da MS e EB, em novilhos alimentados com dietas concentradas e adaptados com monensina (Beede et al, 1980, citados por SCHELLING, 1984.…”
Section: Resultsunclassified
“…Callaway et al (1997) also found that monensin and nicin inhibited starch fermentation in vitro by 30 and 60 %, respectively. Beede et al (1986) designed an experiment to study the effect of monensin on N utilization by growing steers and goats fed diets low in crude protein and measured apparent dry matter, gross energy, fiber digestibilities and growth performance of growing goats.…”
Section: Effect Of Monensin On Protein Metabolismmentioning
confidence: 99%
“…Monensin fed cattle have shown better performance and efficiencies. When Goodrich et al (1984) Beede et al (1986) conducted two digestion and metabolism trials to determine effects of monensin in low-protein diets. In the first experiment they fed 303 kg steers with a control diet that contained 8.7 % crude protein and monensin in the amount of 27 mg/kg of diet dry matter.…”
Section: Effect Of Monensin On Performancementioning
confidence: 99%